Don Quixote of La Mancha - Cervantes Saavedra, Miguel de, 1547-1616.; Starkie, Walter, 1894- (New York : Mentor, 1957)
The epic tale of an eccentric country gentleman and his companion who set out as a knight and squire of old to right wrongs and punish evil in sixteenth-century Spain.
"An abridged version" --t.p.
Adult
Adult
Keywords: Knights and knighthood -- Fiction; Spain -- Fiction; Knights and knighthood -- Fiction; Spain -- Fiction; Picaresque literature; Adventure fiction